EFEKTIVITAS METODE MEMOTIVASI STUDI MURID DENGAN CARA PROBLEM SOLVING KHUSUS PEMBELAJARAN MATERI ILMU FIQIH DI MADRASAH ALIYAH "MIFTAHUL ULUM" DESA NGEMBAL KECAMATAN TUTUR KABUPATEN PASURUAN KELAS XI, TAHUN PELAJARAN 2018-2019 - M Jamhuri (Universitas Yudharta Pasuruan, 2019)
Motivation is an invitation or encouragement to students by using a method or method so that students can increase the spirit of learning with their own awareness without any coercion from anyone including the teacher, so that with the motivation of the teacher students are more likely to pursue lessons than others either at home or at school. Many parties who indicate the low quality of education today is closely related to the low motivation of students. In order to solve learning problems such efforts need to be made efforts, which include the development of learning strategies that are able to optimize student learning motivation in order to improve the quality of overall learning in learning. The formulation of the problem is How is the influence of the problem solving method (problem solving) on ​​increasing the learning spirit of students of class XI M.A "MIFTAHULULUM" Ngembal? What are the advantages and disadvantages of problem solving methods in teaching and learning activities? With the application of problem solving methods (problem solving) in class XI M.A MIFTAHUL ULUM Ngembal, the student's learning spirit is increasing as evidenced by the number of students who often argue in solving a problem using literature that has been read and active. The advantages of applying problem solving methods (problem solving) students can actively participate in teaching and learning activities and think more critically than before, so that the classroom atmosphere becomes more alive. Weaknesses of application to implement problem solving methods, namely the provision of reading books as supporting materials. And the time required is relatively long because students usually require time to think so that their opinions are correct and correct.